2014
DOI: 10.1111/aas.12333
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone for pain after outpatient shoulder surgery: a randomised, double‐blind, placebo‐controlled trial

Abstract: Although our data supported a dose-response relationship, increasing the dexamethasone dose from 8 to 40 mg did not improve analgesia significantly after outpatient shoulder surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…It is possible that dexamethasone at this dose had an effect because it was given before surgery: the meta‐analysis suggested that pre‐operative administration was more effective than intra‐operative administration. An intravenous dexamethasone dose of 40 mg had similar effects to a dose of 8 mg on postoperative pain or analgesic consumption after arthroscopic shoulder surgery, suggesting an upper limit to a dose–response relationship .…”
Section: Discussionmentioning
confidence: 87%
“…It is possible that dexamethasone at this dose had an effect because it was given before surgery: the meta‐analysis suggested that pre‐operative administration was more effective than intra‐operative administration. An intravenous dexamethasone dose of 40 mg had similar effects to a dose of 8 mg on postoperative pain or analgesic consumption after arthroscopic shoulder surgery, suggesting an upper limit to a dose–response relationship .…”
Section: Discussionmentioning
confidence: 87%
“…Six of the included studies used a low dose (4–5 mg) of dexamethasone . Twenty‐six included studies used an intermediate dose of dexamethasone (8–10 mg) . Seven groups studied a high dose of dexamethasone (12–20 mg) .…”
Section: Resultsmentioning
confidence: 99%
“…Two studies were conducted with an open‐label control group, which received a placebo and two studies were conducted in a blinded fashion; however, the control group did not receive a placebo . All other studies were blinded and were conducted with a placebo group . In 20 studies, participants with diabetes were eligible for inclusion in their respective studies .…”
Section: Resultsmentioning
confidence: 99%
“…Intravenous and perineural administration seems to be equivalent in concern to the adjuvant analgesic effect on ISNB [ 61 ]. If the dose is increased the analgesic effect is not prolonged [ 62 ]. Low doses of perineural dexamethasone, like 4 mg, increases the duration of ropivacaine 0,75%.…”
Section: Anesthetic Management Of the Patient With Chronic Shoulder Imentioning
confidence: 99%